(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
Understanding of the reaction kinetics can provide valuable information for the design and optimization of a reaction process. In this study, the reduction degree and carbonitriding ratio of TiO2 in the CH4-H2-N2 system were investigated to understand the carbonitriding reduction kinetics. The experimental results revealed the following key findings. The reduction degree of TiO2 showed a significant increase within the temperature range of 1000 °C to 1200 °C. Simultaneously, the complete carbonitride time decreased as the temperature increased. However, it was observed that excessively high temperatures (1200 °C) had a detrimental effect on the reduction degree. Consequently, the optimal reduction temperature was determined to be 1100 °C, enabling a balance between reduction degree and reaction time. The carbonitriding reduction process of TiO2 in the CH4-H2-N2 system exhibited conformity with the unreacted nuclear model, with chemical reactions primarily controlling the process. A calculated apparent activation energy of 99.35 kJ/mol was obtained for the carbonitriding reduction process. The identification of the optimal reduction temperature and the dominant role of chemical reactions offer valuable insights for the design and optimization of carbonitriding processes involving titanium compounds.